Improvement of Hemifacial Spasm Following Palliative Embolization of an Unruptured Cerebellar Arteriovenous Malformation - Merlin Prisilia Kastilong; Fritz Sumantri Usman; Achmad Firdaus Sani; Gilang Nispu Saputra; Octavianus Darmawan; Rahmi Muin; Leny Kurnia; Erman Keneddy (Neurointervention Working Group of Indonesian Neurological Association, 2025)
Highlight: Cerebellar region's AVM and hemifascial spasm Embolization AVM and hemifacial spasm ABSTRACT Introduction: Posterior fossa arteriovenous malformations (AVMs) are uncommon, accounting for 7–15% of all intracranial AVMs. These malformations typically present with symptoms such as headaches, seizure, and intracerebral hemorrhage. Reports of hemifacial spasm–characterized by involuntary contractions of the facial muscles–as a presenting symptom of AVMs are extremely rare and usually occur only when the facial nerve is compressed. Case: A 35-year-old male presented with worsening left-sided hemifacial spasm, unresponsive to medication for around one year, followed by progressive headache and dizziness. T2-weighted MRI revealed contact between the facial nerve root and a tortuous posterior inferior cerebellar artery (PICA), along with an AVM in the left cerebellar hemisphere. Cerebral angiography demonstrated a left cerebellar AVM with feeding arteries from superior cerebellar artery (SCA) and PICA. The patient underwent successful embolization of the SCA using glue (n-BCA:lipiodol). An intraprocedural thrombus developed but was managed appropriately. Post-procedural cerebral angiography revealed recanalization of the basilar artery and left PICA, with a 30% reduction in nidus size. The hemifacial spasm improved significantly after embolization with an HFS-7 score reduction of six points in the first week post-procedure. Conclusion: Palliative embolization has shown potential in alleviating symptoms associated with hemifacial spasm and improving quality of life. Careful patient selection is essential to rule out secondary causes of hemifacial spasm and to identify underlying neurovascular contacts.